KINETICS OF BIODEGRADATION OF CASSAVA STARCH - COFFEE GROUNDS BIOPLASTICS IN SOIL AND AQUEOUS MEDIA - Komang Widhi Widantha; Risa Nurin Baiti; I Wayan Padma Yogi Asana; Ni Luh Wisma Eka Yanti; Anisa Fitri (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2026)
The environmental concerns associated with petroleum-based plastics have driven the development of biodegradable alternatives. This study investigates the biodegradation kinetics of cassava starch–coffee grounds bioplastics under soil and aqueous conditions. Bioplastic films were prepared using the solution casting method with 10% (w/w) spent coffee grounds and glycerol as a plasticizer. Biodegradation tests were conducted over 14 days, measuring weight loss at predetermined intervals. The results showed that the bioplastics degraded significantly faster in soil, with 61.3% weight loss within seven days, compared to 34.2% in aqueous media. The degradation trends followed first-order kinetics, indicating that the rate of biodegradation depended on the remaining bioplastic mass. The addition of coffee grounds enhanced biodegradability by promoting microbial colonization and water absorption, while soil conditions accelerated enzymatic breakdown. This study demonstrates that cassava starch–coffee grounds bioplastics are promising sustainable materials, offering a pathway for organic waste valorization and supporting circular economy principles.